The Right to Difference: Identity and Self-Expression in Contemporary Citizenship (Global Journal of Human-Social Science, 2024)
This paper examines how contemporary citizenship is increasingly shaped by diverse personal identities and their public expression. Assuming that contemporary innovations (LGBTQIAPN+ aggregations, the expansion of abortion for women and assistance for consensual individual deaths, studies into differentiated human conditions -objective and subjective -ethnic-racial emergenciestraditional or not -and care for specific corporealities) have unprecedentedly taken on human differences as citizenship rights, the author defends the thesis that the emerging network society stems from a contemporary tendency towards generalized competition for intimate self-exposure. By applying the concept of Agonistic Gift (Marcel Mauss), which referred to competitions between donors of works or activities, it is arguable that contemporaneity is a diversifying sociability because intimacy has become the object of competitive generosity. In order to explore this point, the author inductively selected and analyzed an interview with digital influencer Giovanna Titanero, who was selected because her followers adopt several different or even opposing lifestyles, to discuss the exponential contemporary social plurality and, by recovering the notion of community diversity (Ludwig Feuerbach), concludes that parliamentary self-reforms can make democracies representative of emerging human and cultural diversity.
Keywords: identity; diversity; community; digital influencer; democracy